Theoretical investigation of the two-dimensional V2C2/V2C2F2 as prospective host materials for Li- and Na-ion batteries - Bo Xue; Sylvain Pitié; Haowen Xing; Qingfeng Zeng; Shuyin Yu; Gilles Frapper; Kehe Su (AIP Advances)
Density functional theory calculations were employed to investigate the adsorption properties of Li and Na on the thermodynamically stable two-dimensional (2D) tetragonal vanadium carbide 3 × 3 V2C2 slab. The optimized structures of Lix@2D-V2C2 (x = 1–36) and Nax@2D-V2C2 (x = 1–32) were identified. The thermal stability of Li/Na-loaded 2D V2C2 systems at 600 K was demonstrated through first-principles molecular dynamics simulations, while their dynamical stabilities were analyzed by examining their phonon dispersion curves. The functionalized systems were found to exhibit metallic behavior with a density of states distribution. The results indicate that the metal atoms exhibit low diffusion barriers of 0.022 eV for Li and a negligible value for Na, which suggests rapid charge/discharge processes. The theoretical capacities are 851 mA h g−1 for Li and 757 mA h g−1 for Na when adsorbing two layers of adatoms. The average open circuit voltages were found to be relatively low, at 0.40–0.62 V for Li and 0.19–0.42 V for Na. Moreover, the 2D V2C2 host can maintain structural integrity during lithiation and sodiation processes at 300 and 600 K. These features indicate that the predicted 2D V2C2 compound is a promising candidate for use as an anode material in lithium- or sodium-ion batteries. In addition, F-functionalized V2C2, 2D V2C2F2, can be a cathode material for Li- and Na-ion batteries with higher Li/Na diffusion barriers and smaller energy capacities compared to clean 2D V2C2.